2022
DOI: 10.1007/s10792-022-02339-w
|View full text |Cite
|
Sign up to set email alerts
|

Thicknesses of the retinal layers in patients with Graves’ disease with or without orbitopathy

Abstract: Purpose: Graves' ophthalmopathy (GO) is an in ammatory process that may involve the ocular surface, orbital fat, extraocular muscles, and optic nerves in patients with Graves' disease (GD). We aimed to compare thicknesses of retinal layers in patients with GD with and without GO.Methods: One hundred seven patients with GD (23 with GO (Group1), 84 without GO (Group2)) and eighteen volunteers (Group3) were enrolled. The spectral-domain optical coherence tomography (SD-OCT) is used for ophthalmologic evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…One study found a statistically significant difference between TED patients and controls, while three studies found no difference. [ 12 22 29 30 ] Guo et al . found a significant decrease in combined GCL and IPL thickness between patients with DON or moderate TED and controls by 11.4% and 5.4%, respectively, but no difference between mild TED and controls.…”
Section: Resultsmentioning
confidence: 99%
“…One study found a statistically significant difference between TED patients and controls, while three studies found no difference. [ 12 22 29 30 ] Guo et al . found a significant decrease in combined GCL and IPL thickness between patients with DON or moderate TED and controls by 11.4% and 5.4%, respectively, but no difference between mild TED and controls.…”
Section: Resultsmentioning
confidence: 99%
“…However, the difference in the overall RNFL thickness between the groups with GO and GO IOP was not significant. Other studies also observed RNFL thinning in GO patients without clinical optic nerve dysfunction, particularly in the inferior quadrant [12,16,29]. This suggests the possibility that RNFL damage may occur independently of IOP, and that structural RNFL impairments may exist even in clinically normal findings.…”
Section: Structural and Functional Changesmentioning
confidence: 86%
“…In GO, analysing RNFL helps identify consequences of orbital congestion, optic neuropathy, and changes related to secondary glaucoma. The overall thickness of the RNFL in patients with GO was lower than normal values in the general population [ 29 , 30 ]. However, the difference in the overall RNFL thickness between the groups with GO and GO IOP was not significant.…”
Section: Discussionmentioning
confidence: 99%